Discovery of the Potent Phosphoinositide 3‐Kinase δ (PI3 K δ) Inhibitors. Issue 1 (2nd January 2020) - Lei, Tao; Hong, Yongwei; Chang, Xinyue; Zhang, Zhimin; Liu, Xingguo; Hu, Miao; Huang, Wenhai; Yang, Haiyan
Abstract: The PI3Kδ plays a pivotal role in regulating immune cell function and has recently emerged as a promising therapeutic target in treating various diseases, which draw more and more attention to discover potent PI3Kδ inhibitors in recent years. Starting from structure‐based drug design, a series of derivatives were designed and synthesized as new chemotypes of PI3Kδ inhibitors. The potential compounds were structurally optimized by interaction showed in docking study. In cell‐free kinase activity assays, Homogeneous Time‐Resolved Fluorescence Assay (HTRF) method was performed for evaluating the inhibitory activities against PI3Kδ. Interestingly, the representative compound 4 exhibited potent PI3Kδ activity (IC50 =72 nM), which is comparable to that of positive compound TGR1202. Furthermore, compound 4 showed 15‐fold water solubility than TGR1202. In addition, the tests of compound 4 on anti‐cancer activity against jeko‐1 cancer cell line and cytotoxicity against peripheral blood mononuclear cell (PBMC) suggested high inhibition activity and low toxicity respectively. A series of experiments indicated that compound 4 possessed novel chemical structure and high‐efficiency PI3Kδ inhibition activity, deserving further structural optimization to develop highly potent PI3Kδ inhibitors. Abstract : A series of derivatives were designed and synthesized as new chemotypes of PI3Kδ inhibitors. The docking simulations performed on the representative compound 4 illustrated that the purine‐8‐one establishing hydrogen bonds to Val828 and Glu826 of the hinge residues of PI3Kδ. The quinazolinone ring forms π‐π interaction with Trp760. Meanwhile, the representative compound 4 was found to be the most potent with IC50 value of 72 nM against PI3Kδ, which indicated that compound 4 deserves to develop highly potent PI3Kδ inhibitors.